2019
DOI: 10.1007/s13197-018-3545-8
|View full text |Cite
|
Sign up to set email alerts
|

Coconut milk beverage fermented by Lactobacillus reuteri: optimization process and stability during refrigerated storage

Abstract: This study aimed to establish the optimal conditions of temperature (31-43°C) and coconut pulp concentration in water 1:3-1:9 (w/v) for the growth of Lactobacillus reuteri LR 92 or DSM 17938 in coconut milk beverage, using a central composite face centered design. The optimized conditions were used for analysis of the viability during the fermentation process, pH, production of sugars and organic acids by High Performance Liquid Chromatography (HPLC) and reuterin production. Coconut milk provided adequate subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 33 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…Soybean has dominated for the past decades [ 1 , 9 ], but the portfolio of plant-based raw materials for plant-based fermented products has expanded into other legumes, nuts, seeds, pseudocereals, and cereals [ 2 ]. Soy [ 2 , 3 , 10 ], oat [ 11 ], and coconut [ 12 ] are some of the most popular substrates due to their nutritional value and/or their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean has dominated for the past decades [ 1 , 9 ], but the portfolio of plant-based raw materials for plant-based fermented products has expanded into other legumes, nuts, seeds, pseudocereals, and cereals [ 2 ]. Soy [ 2 , 3 , 10 ], oat [ 11 ], and coconut [ 12 ] are some of the most popular substrates due to their nutritional value and/or their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Coconut milk contains a low carbohydrate content (5.5 g/100 g of product) that can be reduced to 1.32 g/100 g of product after fermentation [ 46 ]. Previous studies reported coconut milk as a favorable medium for probiotic bacterial growth [ 12 ] and for the preservation of cell viability after fermentation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soybean products have dominated for the past few decades [ 5 , 6 ], but the portfolio of plant-based raw materials has expanded into other legumes, nuts, seeds, pseudocereals, and cereals [ 7 ]. Soy [ 7 , 8 , 9 ], oat [ 10 ], and coconut [ 11 ] are some of the most popular substrates due to their nutritional value and/or their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Coconut milk contains a low carbohydrate content (5.5 g/100 g of product) that can be reduced to 1.32 g/100 g of product after fermentation [ 33 ]. Previous studies highlight coconut milk as a favorable medium for probiotic bacterial growth [ 11 ] and for cell viability preservation after fermentation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the fermentation process of the strain DSM 17938 has been well characterized (Burgé et al 2015; Strömberg et al 2017; van Niel et al 2017; Mauro and Garcia 2019), the impact of different fermentation variables on the survival of this strain to freeze-drying and several of the subsequent gastro-intestinal tract (GIT) stress conditions (i.e. low pH and bile salts) has not been deeply explored.…”
Section: Introductionmentioning
confidence: 99%